Persistent secondary spontaneous pneumothorax as a complication of tuberculosis infection: a case report - Ni Made Lintya Andani; Putu Diah Savitri (Intisari Sains Medis, 2022)
Introduction: A pneumothorax is a collection of air outside the lung contained within the pleural cavity. Primary spontaneous pneumothorax (PSP) and secondary spontaneous pneumothorax (SSP) are two types of spontaneous pneumothorax that differ due to the underlying illness. If the patient has a history of pulmonary disease, including tuberculosis infection, SSP may be present. Chest X-rays, chest ultrasonography, and CT scans are imaging tests that can be used to diagnose pneumothorax. We report a case of a 20-year-old man with persistent secondary spontaneous pneumothorax as a complication of tuberculosis infection.Case description: A 20-year-old man complained of shortness of breath two weeks before being admitted to the hospital. He had a story of a TB infection. A chest X-ray and a CT scan were used to assess the patient. The pneumothorax is seen with the sign of reactive old tuberculosis. The surgeon inserted a chest tube drainage to empty the pneumothorax. However, following the assessment, the pneumothorax grew even larger than before.Conclusion: Clinical evaluation should probably be the key determinant of the care strategy and assist with the initial diagnosis. Imaging modalities can help confirm a pneumothorax diagnosis and provide information about the extent of the pneumothorax.